2022
DOI: 10.3329/bjms.v21i3.59580
|View full text |Cite
|
Sign up to set email alerts
|

Study of donor deferral during blood donation: A single centre teaching hospital study

Abstract: Background: Safe blood transfusion can be a crucial lifesaving intervention in many clinical situations.For safe blood products donor selection is the first and foremost measure of blood donation. Objective:Aim of the study to determine the incidence and causes for deferral in blood donors. Materials and Methods: This cross-sectional retrospective study was done at Transfusion medicine department in Delta Medical College and Hospital, Bangladesh during 6 months period. In current study data were extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Also, Hypertension was reported as a common cause of deferral at 11.15%. This nding is in agreement with other studies, which reported proportions of 12.3-14.6% [9][10][11]. Indeed, different rates for hypertension have been reported in different populations of prospective blood donors around the globe ranging from 5.8-29.4% [2,8,12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, Hypertension was reported as a common cause of deferral at 11.15%. This nding is in agreement with other studies, which reported proportions of 12.3-14.6% [9][10][11]. Indeed, different rates for hypertension have been reported in different populations of prospective blood donors around the globe ranging from 5.8-29.4% [2,8,12].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported low hemoglobin as a major cause of pre-donation deferrals [2,3,[6][7][8]. Other studies documented hypertension as the cause of the pre-donation deferrals [2,[8][9][10][11][12], while yet another studies found hypotension to be a reason for pre-donation deferrals [11,13,14]. Other reasons for pre-donation deferrals includes: underweight, behavioral risks, low or high pulse rate, being on medication, age related reasons, blood group mismatch among others [2, 3, 9-12, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…One study by Haque et al [18] has deferred 4.26% donors due to wrong Blood group which is much lower than our study. These individuals were also included in the donor pool and they were added as a deferred donors.…”
Section: Table 5 Comparison Of Donor Deferral Percentage In Various S...contrasting
confidence: 73%
“…Donor deferral rate in our study was 19.1% which was higher than many other studies from India. A study done by Haque et al [18] from Bangladesh had comparable deferral rates. The variation in deferral rate can be attributed to many causes like variation in donor selection criteria and type of donors.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation